If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 78 = 2(m + 3) + M Reorder the terms: 78 = 2(3 + m) + M 78 = (3 * 2 + m * 2) + M 78 = (6 + 2m) + M Reorder the terms: 78 = 6 + M + 2m Solving 78 = 6 + M + 2m Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '-1M' to each side of the equation. 78 + -1M = 6 + M + -1M + 2m Combine like terms: M + -1M = 0 78 + -1M = 6 + 0 + 2m 78 + -1M = 6 + 2m Add '-78' to each side of the equation. 78 + -78 + -1M = 6 + -78 + 2m Combine like terms: 78 + -78 = 0 0 + -1M = 6 + -78 + 2m -1M = 6 + -78 + 2m Combine like terms: 6 + -78 = -72 -1M = -72 + 2m Divide each side by '-1'. M = 72 + -2m Simplifying M = 72 + -2m
| .5y=2-2x | | 7x+13=41 | | 2d-15=3 | | -8n-=7n | | -7+5p=-6p-6 | | -5c-12-5c=18 | | 2x+6y=14 | | 13ax+3xa+x= | | 3a=10+5a | | -7x-16=33 | | -d+7=11 | | -14=x-12 | | 2y=22-5x | | 4x=3y-10 | | 3v^2-10v-8=0 | | 5k^2+6k-1=0 | | -10v^2=13v+3 | | 2y+5=1y-23 | | 5x+-36=24+2x | | -3x+15=-6 | | 3x-35=49 | | -4+9=-15 | | 13-9x=113-44x | | (24Q-Q^2)-(20+8Q+Q^2)=0 | | -6+5a=-6(5a+1)-2a | | 4+v=E+2 | | 2y+5=y-23 | | 2x^2-x-14=0 | | 2x+7=22 | | 7y-5=4x+10 | | 2=x/2 | | 360-83= |